Osteoinducing scaffolds with multi-layered biointerface. (6th June 2018) - Grebenik, E A; Grinchenko, V D; Churbanov, S N; Minaev, N V; Shavkuta, B S; Melnikov, P A; Butnaru, D V; Rochev, Yu A; Bagratashvili, V N; Timashev, P S
Abstract: This study was aimed to design and characterise hybrid tissue-engineered constructs composed of osteoinducing polylactide-based scaffolds with multi-layered cellular biointerface for bone tissue reconstruction. Three-dimensional scaffolds with improved hydrophilic and osteoinducing properties were produced using the surface-selective laser sintering (SSLS) method. The designed scaffold pattern had dimensions of 8 × 8 × 2.5 mm and ladder-like pores (∼700 μ m in width). Hyaluronic acid-coated polylactide microparticles (∼100 μ m in diameter) were used as building blocks and water was used as the photosensitizer for SSLS followed by photocross-linking with Irgacure 2959 photoinitiator. Resulting scaffolds provided successful adhesion and expansion of human bone marrow mesenchymal stromal cells from a single-cell suspension. Induced calcium deposition by the cells associated with osteogenic differentiation was detected in 7–21 days of culturing in basal medium. The values were up to 60% higher on scaffolds produced at a higher prototyping speed under the experimental conditions. Innovative approach to graft the scaffolds with multi-layered cell sheets was proposed aiming to facilitate host tissue-implant integration. The sheets of murine MS-5 stromal cell line exhibited contiguous morphology and high viability in a modelled construct. Thus, the SSLS method proved to be effective in designing osteoinducing scaffolds suitable for the delivery of cell sheets.